Price Subsidy Policy in Brazilian Agriculture:: Peculiarities and Contradictions - Abreu, Douglas Paranahyba de; Paranaiba, Adriano de Carvalho; Wander, Alcido Elenor (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2018)
The present article aims to indicate the peculiarities and contradictions found in the price subsidy policies in Brazilian agriculture in the last decade. Despite State efforts carried out through the Minimum Prices Guarantee Policy (PGPM, in the original Portuguese), they have not been a good alternative for several producers. The Austrian School interpretation indicates that the information is not available in a homogenous way to economic agents and price interventions regarding the grant of subsidies, it bears unrevealed costs that raise the information asymmetry of the candidates for the minimum price policy, being unable to reach its objective of reducing such market information asymmetry.